Analisis Keterampilan Menulis Artikel Ilmiah melalui Implementasi Pembelajaran Berbasis Riset pada Mata Kuliah Sains - Muhammad Syazali; M. Liwa Ilhamdi (Departement of Mathematics Education, 2023)
Several learning facilities have been provided, but the writing skills of PGSD students have not reached the very good category. This indicates the need to use other learning facilities. The purpose of this research is to analyze students' skills in writing scientific articles through the implementation of research-based learning. We carried out this pre-experimental research at the PGSD Study Program, University of Mataram. The sample is determined purposively. Scientific articles written by each student are used as qualitative data instruments. The data that has been collected is analyzed descriptively. The findings that we obtained from the study were that the highest score achieved by students was 87.23. The grade for this grade is A and the interpretation is very good. The lowest value is 31.31 (grade E) with very poor interpretation. Classically, the score of scientific article writing skills is 74.05 (grade B+) with good interpretation. From the results of the proportion analysis it is known that grade A has the highest percentage (38.71%). Judging from its aspect, the part that is most mastered by students is writing the identity of the article, introduction, results and discussion, and conclusions. The achievements in these sections have been interpreted very well, where the range of quantitative values is 81.94 – 100. From the results of this study it can be concluded that students' skills in writing scientific articles are good because of the implementation of research-based learning.